Manifestos as an extended marketing campaign - White, Andrew (Palgrave Macmillan, 2016)
Manifestos are one of the main means by which parties project their ‘brand’, chiefly by presenting policy prescriptions which collectively position them at clearly identifiable points along the political spectrum. This chapter focuses on the manifesto as a platform to project each party’s brand, as well as how that brand is communicated to the electorate through mini-campaigns and media events. Space does not allow a consideration of all policies; so, given that it was a key concern of the public, was central to the campaign and featured prominently in the main parties’ manifestos, economic policy is the main focus of this analysis. Overall, the chapter contends that the Conservative brand narrative was the clearest and most credible, which may have contributed significantly to their election victory.